OPTIMIZING STUDENT LEARNING QUALITY THROUGH DIFFERENTIATED INSTRUCTION APPROACHES - Fathi Hidayah; Eny Susiani; Ana Aniati; Bannaga Taha Hussen (Nurul Jadid University, 2024)
This study aims to improve the quality of learning in madrasahs through the application of differentiated learning strategies. Differentiated learning is an approach that adapts teaching methods to the needs, interests, and learning styles of each student. This study is based on the application of strategies in madrasah which are expected to optimize the potential of diverse students and improve overall learning outcomes. This study uses a qualitative case study approach. Data collection techniques are carried out by means of interviews, observations and documentation. The data analysis technique for this study was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that monitoring and feedback in differentiated learning strategies in madrasahs are very important to improve the quality of learning. Routine monitoring by teachers and constructive feedback help students understand the material better. Aspects such as frequency of monitoring, quality of feedback, student participation, and parental involvement contribute to the effectiveness of the strategy, creating an inclusive learning environment for the development of each student. The findings are expected to contribute to the application of differentiated learning strategies which are a significant step in efforts to improve the quality of education in madrasah.